Makna Al-Ḥamd dan Al-Syukr dalam Tafsir - Eva ‘Uyuni Maesyaroh (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2021)
This article discusses the interpretation of the words al-ḥamd and al-syukr. The word al-ḥamd is commonly used in everyday life as a compliment or an expression of gratitude for the pleasure obtained, in Arabic the word ḥamd is equated with the words thanā`, madḥ, ni'ma, and syukr. but not found in the Al-Qur'an except the words ḥamd, syukr, and ni'ma. It is stated that in the Qur'an many words are mutarādif but in fact have their own connotations, referring to this, of course, contains different explanations both in terms of meaning and usage. Therefore, a special study through interpretation is needed because in the interpretation it is found that the two words are disputed. In analyzing these two words using the approach of the muqarran interpretation method on verses related to al-ḥamd and al-syukr in the Al-Qur'an which focuses on the views of al-Ṭabarī, al-Qurṭubī and ibn Kathīr. The aim that the writer wants to achieve in this study is the disclosure of al-ḥamd and al-syukr according to tafsir scholars.